Figli/e orfani/e per femminicidio e famiglie affidatarie. Il ruolo educativo del tutor familiare nel complesso intreccio tra traumi, diritti e bisogni di sviluppo - Mancaniello, Maria Rita (Rivista Italiana di Educazione Familiare, 2022)
Bereavement for mother’s death, by father, or, in any case, murdered by their agent of fatherly care, is a trauma that, for children and adolescents, risks to become insurmountable, unless specific interventions are activated, both at personal support level, and concerning life contexts, where they are placed. In particular, foster families find themselves in the situation of managing a complexity of sorrows and traumas, requiring a great capacity of relational models’ re-elaboration and of new situation’s handling. In this purpose, we consider it as fundamental to form a specific socio-educative professional figure, with interdisciplinary competences, with the role of family tutor, able to support and to accompany children, adolescents and family system. A highly specialised profile, dealing with bereavement handling and elaboration, with work of support and able to create the conditions for a significant undertaking into care, by the multi-professional team, and to make effective and operational the guarantees defined, in Italy, by Law n. 4/2018, for orphaned children and adolescents, due to domestic crimes and for foster families.